The drinking gourd - Monjo, F. N.; Brenner, Fred (New York, Harper & Row, 1970)
Sent home alone for misbehaving in church, Tommy discovers that his house is a station on the underground railroad.
Wilson's Children
Elem. School Library Collection
School Library Journal
3.4
K-3
Keywords: Underground railroad -- Fiction; Underground railroad -- Fiction